A comparison of key attributes between peer-to-peer accommodations and hotels using online reviews. Issue 5 (3rd March 2020) - Zhang, Guojie; Cui, Rui; Cheng, Mingming; Zhang, Qiqi; Li, Zhiyong
ABSTRACT: The advent of peer-to-peer (P2P) accommodation challenges the conventional business practices of long-established accommodation providers such as hotels. Relevant knowledge is needed to identify the key similarities and differences between P2P accommodation and hotels. Using online reviews, this research casts light on guests' perceived differences between Airbnb and hotels. Our research shows that the key differences between Airbnb and hotels are largely reflected through a wide variety of distinctive and similar attributes. The key differences include the ability to bring pets and the opportunity to encounter hosts' pets, atmosphere, flexibility, value for money and quality assurance. This paper provides further insights into knowledge pertaining to the relationship between P2P accommodation and hotels.